2006
DOI: 10.1107/s1600536806030066
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl 4-[4-(benzoyloxy)phenyl]-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate

Abstract: Key indicatorsSingle-crystal X-ray study T = 273 K Mean (C-C) = 0.003 Å R factor = 0.050 wR factor = 0.134 Data-to-parameter ratio = 13.2 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Atom C20 is disordered over two sites with a site-occupation factor of 0.842 (7) for the major conformer (C20A). The bond lengths and angles of the 1,4-DHP ring (Table 1) are comparable to those reported for similar structures (Sundar et al, 2006, and references therein). The substituted 1,4-DHP ring has a flattened boat conformation [puckering parameters (Cremer & Pople, 1975) Q = 0.328 (2) Å , q 2 = 0.316 (2) Å , q 3 = 0.088 (2) Å , = 74.6 (3) and ' = 181.2 (3) for the atom sequence N1-C2-C3-C4-C5-C6], with atoms N1 and C4 deviating by 0.169 (2) and 0.387 (3) Å , respectively, from the base of the boat.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Atom C20 is disordered over two sites with a site-occupation factor of 0.842 (7) for the major conformer (C20A). The bond lengths and angles of the 1,4-DHP ring (Table 1) are comparable to those reported for similar structures (Sundar et al, 2006, and references therein). The substituted 1,4-DHP ring has a flattened boat conformation [puckering parameters (Cremer & Pople, 1975) Q = 0.328 (2) Å , q 2 = 0.316 (2) Å , q 3 = 0.088 (2) Å , = 74.6 (3) and ' = 181.2 (3) for the atom sequence N1-C2-C3-C4-C5-C6], with atoms N1 and C4 deviating by 0.169 (2) and 0.387 (3) Å , respectively, from the base of the boat.…”
supporting
confidence: 86%
“…The mean plane of the 1,4-DHP ring, defined by atoms C2, C3, C5 and C6, makes angles of 26.4 (2) and 15.4 (2) with the C3/C4/C5 and C2/N1/C6 planes. A similar observation has been reported for dimethyl 4-[4-(benzoyloxy)phenyl]-2,6-dimethyl-1,4dihydropyridine-3,5-dicarboxylate (Sundar et al, 2006). The sum of the absolute values of the internal torsion angles of the 1,4-DHP ring is a measure of the planarity.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Considerable downfield shifting of the aromatic protons of the phenyl ring attached at 4‐position of dihydropyridine nucleus due to ester linkage was also observed. X‐ray crystallography studies of DHPs 9a and 9c were also carried out to further authenticate the structures and to study their three‐dimensional orientations [Sundar et al., ,b]. A literature survey has revealed that DHPs with an unsymmetrical ester substitution are, in general, more potent than symmetrically substituted derivatives due to a gain in bulk at the port side ester, which presumably interacts with a hydrophobic receptor domain [Mannhold, ].…”
Section: Resultsmentioning
confidence: 99%